2017
DOI: 10.15376/biores.12.2.2673-2689
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Static and Fatigue Behavior of CFRP-Balsa Sandwiches under Three-point Flexural Loading

Abstract: Balsa wood is a natural cellular material with an excellent resistance-toweight ratio that is ideal for manufacturing the core of sandwich structures. In this study, sandwich specimens with a carbon-fiberreinforced polymer (CFRP) skin and a balsa wood core were tested with static and dynamic loading. Three-point flexural tests in static regime determined the mechanical characteristics of the CFRP-balsa specimens that were needed for subsequent fatigue strength tests. Also, experimental research was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…When the core sandwich is thick enough, an indentation mode occurs firstly, but the sandwich structures will finally fail in a face yield failure mode (first phase), of the upper skin, under sufficient impact energy [ 31 ]. A second phase consists of the onset of the crack of the diamond core and the subsequent propagation of the crack to the lower skin [ 32 ]. The sandwich structures with corrugated core showed a debonding between the skin and the core mainly due to the small contact surface between them ( Figure 10 c).…”
Section: Resultsmentioning
confidence: 99%
“…When the core sandwich is thick enough, an indentation mode occurs firstly, but the sandwich structures will finally fail in a face yield failure mode (first phase), of the upper skin, under sufficient impact energy [ 31 ]. A second phase consists of the onset of the crack of the diamond core and the subsequent propagation of the crack to the lower skin [ 32 ]. The sandwich structures with corrugated core showed a debonding between the skin and the core mainly due to the small contact surface between them ( Figure 10 c).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the severe susceptibility of sandwich structures to impact events many works concentrated on the dynamic response of these bio-based composites addressing their fatigue behavior with both synthetic fibers [27] and natural fibers [28] skins, the low velocity impact behavior in comparison with the one of more traditional PVC foams [29,30], the high strain rate behavior in compression [31], the ballistic response [32] and the residual properties after impact both in compression [33] and bending [34]. The comparison of low velocity impact response of balsa wood and PVC foams sandwich composites proposed by Atas and Sevim [30] demonstrated that for low energy impacts balsa wood structures are characterized by a higher bending stiffness that determines a lower deflection and a higher contact force.…”
Section: Balsa Woodmentioning
confidence: 99%
“…Balsa çekirdekli yapılara ait hasar tiplerini belirlemiş ve S-N eğrilerini oluşturmuştur. Yapıya ait maksimum normal gerilme ve maksimum kayma gerilemelerini belirlemiştir [11]. Özdemir ve diğ., farklı çekirdek kalınlıklarındaki (15mm ve 20mm) balsa odunlarının kullanıldığı sandviç kompozitlere tekil ve tekrarlı düşük hızlı darbe deneyi uygulamıştır.…”
Section: Literatür öZetiunclassified